PENGARUH MEDIA PEMBELAJARAN DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR SISWA KELAS XI ADMINISTRASI PERKANTORAN - Johan Krisna; Cicilia Dyah Sulistyaningrum Indrawati; Patni Ninghardjanti (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2022)
This study used a descriptive research method with a quantitative approach. Thesampling technique used the saturated sample technique. Methods of collectingdata used the questionnaire and the documentation. The results of this study are asfollows there is a significant positive effect of learning media on learningachievement. This is based on the value of tcount>ttable, which is 2.645 > 1.673 ata significance level of 5%. There is a significant positive effect of learningachievement on learning achievement. This is based on the value of tcount>ttablewhich is 4.564 > 1.673 at a significance level of 5%. Tthere is a significant effectof learning media and learning motivation together on learning achievement. Thisis based on the value of Fcount>Ftable which is 18.118 > 3.162 at a significancelevel of 5%. The amount of the relative contribution of learning media by 28.24%.The relative contribution of learning motivation is 75.76%. The effectivecontribution of learning media is 11.10%. The effective contribution of learningmotivation is 18.20%.